Micropenis - Rahman, Shahin Ibn; Huq, Nausher Azimul; Agarwala, Bimol Kumar (Journal of Dhaka National Medical College & Hospital, 2021)
Micropenis is a medical diagnosis based on correct measurement of penile length. If stretched penile length is below the value corresponding to - 2.5 standard deviation of the mean in a patient with normal internal and external male genitalia, a diagnosis of micropenis is considered. Micropenis can be caused by a variety of factors including structural or hormonal defects of the hypothalamic-pituitary-gonadal axis. It can also be a component of a number of congenital syndromes. For the etiological evaluation, endocrinologic tests are important. This article reviews the etiology, diagnosis, treatment and management of micropenis. J. Dhaka National Med. Coll. Hos. 2021; 27 (01): 39-42